2021
DOI: 10.5005/jp-journals-10080-1515
|View full text |Cite
|
Sign up to set email alerts
|

Does Retrograde Femoral Nailing through a Normal Physis Impair Growth? An Experimental Porcine Model

Abstract: A bstract Materials and methods The study was carried out using an experimental porcine model. Eleven juvenile female porcines were randomized for insertion of a retrograde femoral nail in one limb. The other limb acted as a control. The animals were housed for 8 weeks before the nail was removed and housed for 8 additional weeks, that is, 16 weeks in total. Growth was assessed by interphyseal distance on 3D magnetic resonance imaging (MRI) after 16 weeks and the operate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…As a previous study found no limb length discrepancy with the placement of nails violating 7% or less of the physis, 2 we suspect that growth inhibition may have occurred with implant removal. This supports a recent study by Abood et al, 3 which found retrograde femoral nailing did not impair growth 8 weeks after nail removal in a porcine model. Our study had longer follow-up of 3 to 5 months after nail removal, with both gross and histologic changes noted between these 2 later time points.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…As a previous study found no limb length discrepancy with the placement of nails violating 7% or less of the physis, 2 we suspect that growth inhibition may have occurred with implant removal. This supports a recent study by Abood et al, 3 which found retrograde femoral nailing did not impair growth 8 weeks after nail removal in a porcine model. Our study had longer follow-up of 3 to 5 months after nail removal, with both gross and histologic changes noted between these 2 later time points.…”
Section: Discussionsupporting
confidence: 91%
“…[12][13][14] However, when a retrograde femoral nail is placed across the physis, growth can continue as long as the nail violates only a subcritical portion of the distal femoral physis. [1][2][3] Despite the significant differences in limb length discrepancy when compared with contralateral control limbs in sheep sacrificed at 3 months after implant removal, evidence of normalization of this discrepancy was appreciated in sheep sacrificed 5 months after implant removal. As a previous study found no limb length discrepancy with the placement of nails violating 7% or less of the physis, 2 we suspect that growth inhibition may have occurred with implant removal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations